2016
DOI: 10.1155/2016/3272530
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TIVA and Desflurane Added to a Subanaesthetic Dose of Propofol in Patients Undergoing Coronary Artery Bypass Surgery: Evaluation of Haemodynamic and Stress Hormone Changes

Abstract: Introduction. Increased levels of stress hormones are associated with mortality in patients undergoing coronary artery bypass grafting (CABG). Aim. To compare total intravenous anaesthesia (TIVA) and desflurane added to a subanaesthetic dose of propofol. Material and Methods. Fifty patients were enrolled in this study. Fentanyl (3–5 mcg/kg/h) was started in both groups. Patients were divided into two groups. The PD group (n = 25) received 1 minimum alveolar concentration (MAC) desflurane anaesthesia in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
(23 reference statements)
0
7
0
3
Order By: Relevance
“…MAP and HR had smaller fluctuations in patients in group S than those in group P. Patients for EVL and EVS in the current study often have acute or chronic blood loss. Propofol may be associated with diminished myocardial contractility, decreased cardiac output, reduced ability of the cardiovascular system to respond to stress (30) and preoperative fasting, all of which lead to relative or absolute hypovolemia (31). Therefore, in the present study, more ephedrine was used in group P than Figure 5.…”
Section: Discussionmentioning
confidence: 90%
“…MAP and HR had smaller fluctuations in patients in group S than those in group P. Patients for EVL and EVS in the current study often have acute or chronic blood loss. Propofol may be associated with diminished myocardial contractility, decreased cardiac output, reduced ability of the cardiovascular system to respond to stress (30) and preoperative fasting, all of which lead to relative or absolute hypovolemia (31). Therefore, in the present study, more ephedrine was used in group P than Figure 5.…”
Section: Discussionmentioning
confidence: 90%
“…Increased secretion of surgical stress response associated hormones could cause tachycardia and elevate myocardial oxygen demand, peripheral vascular resistance, and oxygen consumption. Moreover, α-receptor activated sympathetic nerve stimulation may also lead to contraction of the coronary artery inducing myocardial ischemia [7]. Clinically, administration of anesthetic drugs to alleviate stress, could be effective in decreasing postoperative complications and mortality [8].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In this context, a previous RCT reported that compared with volatile anesthesia, TIVA could control stress and hemodynamic response in patients undergoing CABG. 21 However, there has been no report that TIVA is associated with a better survival outcome than inhalation anesthesia; therefore, the authors' results should be interpreted with care. Although propofol-based TIVA has been reported to lower the inflammatory effect during CABG, 18,19 the major side effect of propofol should be considered.…”
Section: Discussionmentioning
confidence: 89%